Determinants of US Transit Bus Prices - Ayush Pandey; Lewis Lehe (Findings)
Using data from the American Public Transportation Association's 2024 Public Transportation Vehicle Database, this paper estimates statistical models to explain the real prices of single-deck, rigid US transit buses in terms of their attributes. Non-electric bus prices have risen by 0.7% per year faster than inflation since 2010, while electric bus' real prices have fallen by about 3% annually. The elasticity of price with respect to length is only 0.36, such that a 30 ft. (9.1 m) bus is only 10% cheaper than a 40 ft. (12.2 m) bus. High-floor buses are 3.4% cheaper than standard low-floor models. CNG, diesel-electric hybrid and battery electric buses cost, respectively, about 11%, 44% and 66% more than diesel buses. BYD buses are substantially cheaper than those of other manufacturers. The sample of buses is fairly homogeneous except for power type.